Integration of Sufism Values into the Curriculum of Islamic Religious Education Subject in Junior High School - Abitolkha, Amir Maliki; Mas'ud, Ali (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2021)
Sufism is a self awareness, a spiritual vibration, a trajectory in the heart, a whisper of conscience, a feeling of longing that is difficult to express in words. Sufism needs to be integrated in the curriculum of Islamic Religious Education (PAI) as it can affect the process of shaping students' attitudes, behaviors and characters. This article explains the importance of Sufism values combined with PAI materials. Through a literature review of the Junior High School (SMP) Islamic Religious Education books for grades VII-IX, using a content analysis approach, it was found that the PAI materials in general were still textual in nature, and lacked the insertion of Sufism values. Hence, it is urgent to integrate Sufism values into the Islamic Education curriculum, especially at the junior high school level because junior high school students are prone to experiencing moral crises and the process of searching for identity. Gradually, the steps of Sufism which need to be carried out in delivering the PAI materials in junior high school are takhalli (cleansing oneself from bad qualities), tahalli (filling the heart with good qualities), and tajalli (opening of divine light that permeate into oneself). The integration of Sufism values into the Islamic Education curriculum can shape students’ good attitudes and behaviors. Thus, learning PAI material becomes more effective in shaping noble morals for students.